Inventory Management with Stochastic Demand: Case Study of a Medical Equipment Company - Alfaro-Marchant, M; Ternero-Saavedra, R; Sepulveda-Rojas, J; Vargas-Guzman, M; Fuertes-Sanchez, G (Southern African Institute for Industrial Engineering, 2023)
This research proposes an inventory management system based on a periodic review model for a medical equipment company. The work aims to reduce inventory volume and out-of-stock and to improve service levels. The proposed methodology is a combined ABC/XYZ classification using the patterns and magnitude of demand under the constraints of spare parts cost. For the ABC/XYZ classification, we propose a model to forecast demand; and we evaluate eight forecasting methods to adjust the classification characteristics. The results obtained allow the reduction of arrears, an increased service level, and a decrease in average inventory. © 2023, Southern African Institute for Industrial Engineering. All rights reserved.